Compassion Fatigue and Workplace Well-Being among Healthcare Professionals at Level II Government Hospital in Western Visayas, Philippines - Alojado, Jean T.; Madrigal, Dennis (Technium Social Sciences Journal, 2024)
The study investigated compassion fatigue (CF) and workplace well-being among healthcare professionals in a Level II government hospital in Western Visayas, Philippines. The research aimed to identify potential variations in CF and well-being based on demographics and work-related factors, and to assess the relationship between these two constructs. The study utilized the Compassion Satisfaction and Fatigue Test (CSFT) and the Short Smith Wellbeing (SWELL) Questionnaire for Workers to measure CF and workplace well-being, respectively. The findings revealed that healthcare professionals generally reported low levels of CF and high levels of workplace well-being, regardless of their demographic characteristics or work-related factors. However, significant differences in CF were observed based on age and civil status, with younger and single individuals reporting higher levels of CF. The study also found no significant relationship between CF and workplace well-being, suggesting that other factors may play a more crucial role in influencing well-being. The research concludes by highlighting the importance of addressing CF and promoting workplace well-being among healthcare professionals, particularly those who are younger and single. The findings have practical implications for healthcare organizations, emphasizing the need for targeted interventions and support systems to mitigate CF and enhance the overall well-being of the healthcare workforce.